Facile, Diversity-Oriented, Normal-Electron-Demand Diels–Alder Reactions of 6-Amino-2H-pyran-2-ones with Diethyl Acetylenedicarboxylate, 1,4-Naphthoquinone, and N-Phenylmaleimide - Khatri, Adil I.; Samant, Shriniwas D. (Synthesis, 2015)
A series of 6-amino-4-methoxyphenyl-2H-pyran-2-ones, having an electron-rich diene system, capable of undergoing normal-electron-demand (NED) Diels–Alder reaction, were synthesized. The Diels–Alder reaction of these pyrones with electron-deficient dienophiles – diethyl acetylene dicarboxylate, 1,4-naphthoquinone, and N-phenylmaleimide – followed three different pathways and gave structurally diverse products, aminobenzenes, aminoanthraquinones, and aminopolycyclic diimides, respectively. The amino group at the 6-position activated substantially the pyrone ring towards NED Diels–Alder reaction and the reaction has a potential to generate great structural diversity.
Keywords: 6-amino-2H-pyrone; normal-electron-demand Diels–Alder reaction; diversity-oriented synthesis; aminobiphenyls; anthraquinones; polycyclic diimides